2008
DOI: 10.1063/1.2978376
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of oxygen vacancy on the dielectric and electromechanical properties in ferroelectric ceramics

Abstract: The effect of oxygen vacancy on the dielectric and electromechanical properties in lead titanate zirconate based ferroelectric ceramics is discussed in this paper. The presence of oxygen vacancy forms a defect-dipole inside a perovskite cell. This defect-dipole contributes to the unswitchable polarization and influences the alignment of the ferroelectric dipole in the same cell as well. The latter is due to the displacement of the B-site cation, which contributes to the switchable polarization. It is found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…It should be noted that sintering above 1050°C caused a reaction with the alumina support plate, which precluded the use of sintering procedures at temperatures above this level. The occurrence of tilted and/or constricted P-E loops in ferroelectric ceramics can be attributed to several factors 78,79 including domain wall pinning due to oxygen vacancy-cation defect dipoles with related ageing effects, 80,81 the presence of antiferroelectric phases 82,83 or, as reported recently, reversible electric field-induced relaxor ferroelectric to ferroelectric transformations. 84 For undoped BiFeO 3 ceramics, it is commonly reported that the constriction phenomenon is associated with 'domain wall pinning' by defect dipoles.…”
Section: Ferroelectric Propertiesmentioning
confidence: 67%
“…It should be noted that sintering above 1050°C caused a reaction with the alumina support plate, which precluded the use of sintering procedures at temperatures above this level. The occurrence of tilted and/or constricted P-E loops in ferroelectric ceramics can be attributed to several factors 78,79 including domain wall pinning due to oxygen vacancy-cation defect dipoles with related ageing effects, 80,81 the presence of antiferroelectric phases 82,83 or, as reported recently, reversible electric field-induced relaxor ferroelectric to ferroelectric transformations. 84 For undoped BiFeO 3 ceramics, it is commonly reported that the constriction phenomenon is associated with 'domain wall pinning' by defect dipoles.…”
Section: Ferroelectric Propertiesmentioning
confidence: 67%
“…In contrast, the P-E loops of the LaBa ceramics exhibit a pinched, or constricted, shape (Figure 5(b)). Previous studies have attributed this type of constrained ferroelectric switching to the presence of antiferroelectric phases, 82,83 domain wall pinning by oxygen vacancycation dipolar defects, 84,85 or reversible electric field-induced relaxor to normal ferroelectric transformations. 86 The constricted loops observed in unmodified BiFeO 3 ceramics were attributed to domain wall pinning by defect dipoles.…”
Section: Ferroelectric Propertiesmentioning
confidence: 95%
“…Such a polar defect symmetry will produce a defect dipolar moment (P D ) aligning along P S direction (fig. 3(a2)), and thus it will build an internal field [11,12,30,31] along P S to stabilize each domains state (fig. 3(b2)).…”
mentioning
confidence: 99%